Leserbrief zum Beitrag MRg-HIFU (doi:10.1055/a-0817-5645) - Holger Strunk; Tolga Tonguc; Milka Marinova (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2019)
Abstract This cross-sectional study investigated trabecular bone score, fracture risk assessment tool, and bone mineral density in relation to exercise and body composition in postmenopausal women. Fifty-eight postmenopausal women grouped as sedentary, runners, swimmers, or high intensity exercisers participated in this study. Dual-energy X-ray absorptiometry scans measured total and regional body composition and bone mineral density. Trabecular bone score and fracture risk assessment tool were also assessed. Analysis of covariance with Bonferroni post hoc testing was used to assess group differences while controlling lean mass, years postmenopause, and exercise history. Linear regression examined relationships between body composition and bone outcomes while controlling for years postmenopause and past exercise. Age and years postmenopause were not different between groups. There were no differences in total or regional lean mass, bone mineral density, trabecular bone score, or fracture risk assessment tool between groups. Independent of group, total lean mass and body weight positively associated with total, arm, leg bone mineral density and total bone mineral content (all p<0.05). Total lean mass was also positively associated with trunk bone mineral density (p=0.04), but negatively with fracture risk assessment tool (p=0.01) and trabecular bone score-adjusted fracture risk assessment tool (p=0.03). No differences in lean mass or bone outcomes were observed between groups. However, total lean mass and body weight were positively associated with multiple bone outcomes including hip fracture risk, emphasizing the importance of preserving muscle throughout menopause.